Production And Characterization Of Ultraviolet Cured Palm Oil Based Resin - Tai, Nyok Ling (2012)
In this study, a Ultraviolet-radiated curable resin from palm oil was prepared by modifying palm oil with glycerol and glycidyl methacrylate (GMA). In the preliminary study, different parameters such as the amount of catalyst needed, reaction temperature and time for this chemical modification had been studied. From the Fourier Transform Infrared (FTIR) analysis, GMA was proved to be chemically attached to the monoglyceride (MG), an increment at peak 1630 cm-1 in FTIR spectrum was observed when more GMA was used in the chemical modification. In the subsequent study, the effect of different glycerol/palm oil (MG) to GMA/MG ratio in the preparation of MG-GMA resin was studied.